Analyzing the Effects of Demographic Transition on Child Labor in Developing Economies - Ruqayya Ibraheem; Altaf Hussain; Rashid Ahmad; Tusawar Iftikhar Ahmad (Sustainable Business and Society in Emerging Economies, 2022)
Purpose: In efforts to realize the dividend of demographic transition, elimination of child labor has become an utmost challenge for the relevant international bodies. Knowing the importance of this issue, children are now the center of the vision of sustainable development as SDG 8.7 and 16.2 are directly related to children and their lives. In this context, the purpose of the current study is to analyze the linkages between demographic variables (such as working-age population, labor force participation rate, labor force growth rate, life expectancy, and dependency ratio and population growth) and child labor along with some other macroeconomic determinants of child labor.